PHYSICAL CHARACTERISTICS OF KEPOK, TALAS, AND CAVENDISH BANANAS FLOUR - Krishna Purnawan Candra; Anis Sofianur; Bernatal Saragih; Yuliani Yuliani (Food ScienTech Journal, 2021)
Banana flour is one of the semi-finished products which processed aims to maintain shelf life, provide goods for diver food products, facilitate packaging and transportation. This research aimed to determine and compare the physical characteristics of flour from three banana species, i.e., Kepok (Musa acuminata x balbisiana), Talas (Musa acuminata Colla var. Talas), and Cavendish (Musa acuminata Colla var. Cavendish). This research is a single factor experiment arranged in a completely randomized design with three (banana species) treatments and five replications. Data were analyzed by ANOVA except for wettability data, and gelatinization profile is processed using the Kruskal-Wallis test. The experimental parameters were swelling power, starch solubility, bulk density, water absorption capacity, oil absorption, and color. The results showed that swelling power and oil absorption of the banana flour from the three banana species are not significantly different (p > 0.05) but significantly different (p < 0.05) for solubility, bulk density, wettability, water absorption capacity, and color. Gelatinization temperature for Kepok, Talas, and Cavendish banana flour was 79.45°C, 81.45°C, and 78.20°C, respectively. In this research, we found that the physical properties of Talas banana flour are in between the physical properties of Kepok and Cavendish banana flour.